The concept of musibah in the Qur'an : an analytical study - Jalaluddin bin Hassan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The world has been facing from the time immemorial natural as well as man-made disasters and calamities. It seems the natural as well as man-made disasters in the modern times are outstripping those in the past. Human reactions to these phenomena have been various. Some consider them the fury of God against the sin of man on the earth. Some deem the catastrophe as injustice of God. Some think that the catastrophes reflect the test of man. Some lose, in response to the disasters, their faith in God. Some get their faith in God more strengthened after suffering from difficult situations. What is the wisdom of disasters of the earth? What should be proper reactions and response to such events? What is the Qur'anic guidance in this regard? This research is devoted to study these questions with the intention of coming up with an appropriate view as available in the Qur'an. The methodology applied in this study is analytical. The conclusion reached for this research is that natural and man-made catastrophes on the earth serve as tests for mankind as well as reminders to them of their transgressions on this earth. They are at times may be concluded as divine punishment to man and his society for their wrongdoings on the surface of this earth.